KONTRIBUSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER ISLAM MODERAT - Maisaroh, Siti; Arifin, Zainal (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Asy-Syafa'ah Middle School is a school that has students from various ethnicities, customs and beliefs, such as students who come from Javanese, Madurese descent, and there are also those who come from outside the island, namely from Ambon. With this situation, this junior high school has implemented PAI learning based on religious moderation to deal with various different backgrounds. Therefore, this research aims to describe the contribution of Islamic religious education learning in the formation of moderate Islam for students at Asy-Syafa'ah Jember Middle School. This research is field research with a descriptive qualitative approach. The results of the research show that Asy-Syafa'ah Jember Middle School has internalized the values ​​of religious moderation in PAI learning and integrated it into the development of PAI material. Among the values ​​of Islamic moderation that are internalized are tolerance, balance and justice so that students are able to balance the harmony that exists in society. In order for this learning to run optimally, Asy-Syafa'ah Jember Middle School applies several methods that must be applied by all teaching staff and in the school environment. These methods are example, habituation, and punishment.